The Application of Goat Bone Waste Activated Charcoal As Manganese Heavy Metal Absorbent in Borehole Water - Sari Wardani; Savitri Savitri; Firda Mawardah; Muhammad Adham; Lindawati Lindawati (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2021)
Abstract: Bone is a waste from livestock that contains both organic and inorganic components. It consists of 69% organic compounds used as raw materials for activated charcoal manufacturing. The research aimed to process goat bone waste into activated charcoal products to absorb manganese-heavy metals in borehole water. This research was conducted through carbonization, activation, and characterization. The goat bone waste was carbonized and heated at 700oC for 1 hour, followed by activation. The absorption of manganese-heavy metal was determined by variating the weight of goat bone activated charcoal in 5 g, 10 g, 15 g with a contact time of 15 and 30 minutes. The goat bone waste charcoal obtained was characterized by proximate test, Fourier Transform Infrared Spectroscopy (FT-IR), and Scanning Electron Microscopy (SEM). The results showed that goat bone activated charcoal has a water content value of 2%, ash content of 7%, volatile matter of 10%, fixed carbon 87%, and iodine absorption of 968 mg/g. These values still meet the requirement specified in SNI 06-3730-1995 and SNI 06-4253-1996. The Fourier Transform Infrared Spectroscopy (FTIR) analysis produced functions groups of C–H, C=C, C=H, CºC, N-H dan O–H. The Scanning Electron Microscopy (SEM) test results found an active charcoal pore diameter of 5,200 mm x 12,952 mm. The efficiency of manganese heavy metals absorption in borehole water ranges from 99.707% - 99.821%.Abstrak: Tulang merupakan limbah hasil peternakan yang pemanfaatannya belum maksimal. Tulang tersusun dari senyawa organik sebesar 69% yang dapat dijadikan bahan baku pembuatan arang aktif. Penelitian bertujuan mengolah limbah tulang kambing menjadi produk arang aktif yang mampu menyerap logam berat mangan pada air sumur bor. Metode penelitian meliputi tahap karbonisasi tulang, tahap aktivasi arang pada suhu 700 oC selama 1 jam, tahap penyerapan logam berat mangan mengunakan variasi berat arang aktif tulang kambing 5 g, 10 g, 15 g dengan waktu kontak 15 dan 30 menit dan tahap analisis meliputi uji proksimat, uji gugus fungsi dan uji morfologi. Hasil uji proksimat menunjukkan nilai kadar air 2%, kadar abu 7%, volatile matter 10%, fixed karbon 87 %, daya serap yodium 968 mg/g masih memenuhi SNI 06-3730- 1995 dan SNI 06-4253-1996. Uji FTIR menghasilkan gugus fungsi C–H, C=C, C=H, CºC, N-H dan O–H. Pengujian SEM menghasilkan diameter pori arang aktif sebesar 5,200 mm x 12,952 mm. Efesiensi penyerapan logam berat mangan pada air sumur bor berkisar pada 99,707% - 99,821%.